2013
DOI: 10.1007/s12199-013-0364-4
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory involvements among women exposed to the smoke of traditional biomass fuel and gas fuel in a district of Bangladesh

Abstract: The study shows significant association between biomass fuel use and respiratory involvement among rural women in Bangladesh, although the potential confounding of urban/rural residency could not be ruled out in the analysis. The use of smoke-free stoves and adequate ventilation along with health education to the rural population to increase awareness about the health effects of indoor biomass fuel use might have roles to prevent these involvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 34 publications
9
44
1
Order By: Relevance
“…In order to measure the perception of disease exposure among traders, the knowledge, attitude and 2 The number of cars in Ghana increases by 23%. Alim et al (2014) was adapted to measure the effect of traffic emissions on self-reported health among traders. In order to measure the risk factors associated with illness due to vehicular emissions, respondents were asked to state their perception of the health risks they faced daily during their trading activities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to measure the perception of disease exposure among traders, the knowledge, attitude and 2 The number of cars in Ghana increases by 23%. Alim et al (2014) was adapted to measure the effect of traffic emissions on self-reported health among traders. In order to measure the risk factors associated with illness due to vehicular emissions, respondents were asked to state their perception of the health risks they faced daily during their trading activities.…”
Section: Methodsmentioning
confidence: 99%
“…It forms the basis for assessing progress on human development and growth (Cohen, 2010;Bloom, Canning & Sevilla 2004;Spence & Lewis, 2009). Regardless of the importance of health to human progress, empirical evidence shows that a number of people worldwide suffer from pollution-related illnesses, which include asthma, chronic obstructive pulmonary diseases (COPD), cardiovascular diseases, and lung cancer (Wargo, Wargo, & Alderman, 2006;Alim et al 2014). According to the International Energy Agency (IEA), about 18,000 people worldwide die each day from prolong exposure to air pollution (IEA, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many health studies have examined the respiratory function of women (as main household cooks) using clinical measures such as lung function tests (such as spirometry or peak air flow tests, e.g., Alim et al, ; Kurmi et al, ). An increased risk of physician‐diagnosed chronic bronchitis (OR: 5.94 (95% CI: 1.02–34.45, P < 0.047) and severe bronchial obstruction diagnosed by peak expiratory flow rate (OR: 4.54 (95% CI: 2.10–9.82, P < 0.001) was associated with households using solid biomass compared to households cooking on gas (Alim et al, ). None of the studies accurately measured the extent of child pollution exposure and associated health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The use of solid fuels for cooking has serious repercussions on human health. According to the World Health Organization (WHO), household air pollution (HAP) accounts for more than 4 million deaths every year (WHO 2014) due to harmful toxins released from the inefficient combustion of solid fuels (Perez-Padilla, Schilmann et al 2010, Alim, Sarker et al 2014. Health effects due to HAP are observed more in women and children than men, primarily because women spend more time cooking than men, and children remain in the vicinity of their mothers (Practical Action 2014).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Numerous studies have already documented that cooking with solid fuels has multifaceted detrimental effects on humans (Perez-Padilla, Schilmann et al 2010, Alim, Sarker et al 2014, WHO 2014, social (Practical Action 2014) and environmental health (Hosonuma, Herold et al 2012), and hence they strongly argue for a complete cooking fuel transition towards modern and clean alternatives (Goldemberg, Johansson et al 2004, Modi, McDade et al 2005, Pachauri, Brew-Hammond et al 2012, such as electricity, Liquid Petroleum Gas (LPG), and natural gas. Although the availability of modern energy carriers is a prerequisite for their adoption and sustained use for cooking (Barnes, Khandker et al 2011, Bhide andMonroy 2011), various studies have demonstrated that solid fuel users may not switch to modern cooking fuels and technology even though the latter is available (Masera, Saatkamp et al 2000, Joon, Chandra et al 2009.…”
Section: Introductionmentioning
confidence: 99%